A Literature Review: Understanding TNF and IL-1 of the Main Cause of Thorombo-occlusive in Lucio’s Phenomenon - Erald Giovanny Hasiholan Simatupang; Ulfa Pratiwi; Hayuningrat Odyssey Saint; Dhea Ivanka (Universitas Muhammadiyah Palu, 2023)
Last year, it was 0.5 out of every 10,000 people, but now it has increased. Lucio's Leprosy, also known as Leprosy Bonita, is a very uncommon type of serious leprosy. The Lucio phenomenon is a severe reaction that can occur in individuals with Lucio's leprosy. It causes a skin condition called